Cinnamic Acid, Ethanol and Temperature Interaction on Coumarate Decarboxylase Activity and the Relative Expression of the Putative Cd Gene in D. Bruxellensis - Martinez-Fernandez, C; Ganga-Munoz, M; Garcia-Mena, V; Salinas-Sanhueza, F (2011)
Dekkera bruxellensis is one of the main contaminating yeasts in wine due to its ability to metabolize cinnamic acids into volatile phenols. This yeast metabolizes p-coumaric acid into 4-vinylphenol through a coumarate decarboxylase (CD) and then transforms it into to 4-ethylphenol (EF) through a vinylphenol reductase. In this work we investigated the influence of the interaction between the concentration of p-coumaric acid, ferulic acid and ethanol as well as growth temperature on the production of CD activity and the expression of a putative gene that codes for this enzymatic activity. For this, a Box Behnken experimental design was used. The concentration of p-coumaric acid (5-26 ppm) and ferulic acid (3-9 ppm) alone did not show any significant effect on any of the studied response variables. However, the interaction between (ethanol concentration * cinnamic acid concentration) and (ethanol concentration * temperature) had a significant statistical effect on the production of CD activity. Additionally, a higher growth temperature negatively affected the expression of the putative cd gene and the production of CD activity. This is the first work that studies the effect of cinnamic acids on the production of CD activity and the relative expression of its putative gene, using natural concentrations of cinnamic acid found in wine. © 2011 by Pontificia Universidad Católica de Valparaíso, Chile.